2015
DOI: 10.11648/j.ajam.20150302.16
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study on Unsteady MHD Free Convection and Mass Transfer Flow Past a Vertical Porous Plate

Abstract: The unsteady MHD free convection and mass transfer boundary layer flow past a semi-infinite vertical porous plate immersed in a porous medium with heat source is studied. The plate moves with a uniform velocity in the direction of the fluid flow while the free stream velocity is considered to follow the exponentially increasing small perturbation law. The governing equations are solved analytical by using perturbation technique depending on the physical parameters including the Radiation parameter (R), the Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Due to above significant role, it is the purpose of this paper to examine the effect of viscous dissipation and chemical reaction on the MHD flow of a viscous incompressible fluid past a semi-infinite vertical plate. This flow problem was previously studied by Ahmmed et.al [8] in the absence of these two parameters.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to above significant role, it is the purpose of this paper to examine the effect of viscous dissipation and chemical reaction on the MHD flow of a viscous incompressible fluid past a semi-infinite vertical plate. This flow problem was previously studied by Ahmmed et.al [8] in the absence of these two parameters.…”
Section: Introductionmentioning
confidence: 93%
“…Recently Ahmmed et.al. [8] studied the unsteady MHD free convection and mass transfer flow past a vertical porous plate.…”
Section: Introductionmentioning
confidence: 99%
“…Their conclusions revealed that, velocity profiles decrease with increase in magnetic field. Ahmed et al (2015) examined an analytical study on an unsteady MHD free convection and mass transfer flow past a vertical porous channel. They concluded that fluid velocity increases due to an increase in permeability parameter.…”
Section: Introductionmentioning
confidence: 99%